Overcoming the obstacles of visualization in robotically assisted abdominal cerclage using indocyanine green. Issue 4 (December 2016) - Zeybek, Burak; Borahay, Mostafa; Kilic, Gokhan
Abstract Abdominal cerclage is found to have success rates of 85–95 % with lower incidence of preterm delivery and preterm premature rupture of membranes when compared to the vaginal approach. However, since it is more invasive, its use has been limited to selected cases. Robot-assisted abdominal cerclage is a relatively new minimally invasive technique that gives the opportunity for less invasive procedures when compared to the open technique and, when compared to conventional laparoscopy, has the advantages of 3D visualization and endowristed instrumentation. The distinctive feature of our case is the use of near infrared camera system, which is a relatively new modality in robotics and, to the best of our knowledge, this is the first report in the literature that indocyanine green dye was used to help to visualize vascular anatomy during a robotic cerclage procedure in a pregnant patient.